2006
DOI: 10.1073/pnas.0601552103
|View full text |Cite|
|
Sign up to set email alerts
|

Carboxyethylpyrrole oxidative protein modifications stimulate neovascularization: Implications for age-related macular degeneration

Abstract: Choroidal neovascularization (CNV), the advanced stage of age-related macular degeneration (AMD), accounts for >80% of vision loss in AMD. Carboxyethylpyrrole (CEP) protein modifications, uniquely generated from oxidation of docosahexaenoate-containing lipids, are more abundant in Bruch’s membrane from AMD eyes. We tested the hypothesis that CEP protein adducts stimulate angiogenesis and possibly contribute to CNV in AMD. Human serum albumin (HSA) or acetyl-Gly-Lys- O -methyl ester (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
130
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(135 citation statements)
references
References 36 publications
3
130
2
Order By: Relevance
“…In AMD, CEP adducts are elevated in Bruch membrane (27), the extracellular matrix separating the RPE from the blood-bearing choroid; AMD plasma also contains elevated levels of CEP adducts and CEP autoantibodies (34). Furthermore CEP adducts stimulate neovascularization in vivo (35) and can induce a late stage AMD-like phenotype (geographic atrophy) in a mouse model of AMD (36). Iso [4]LGE 2 , an extraordinarily reactive electrophile belonging to the isolevuglandin family, is generated by free radical-induced oxidation of arachidonyl phospholipids and produces an array of lysyl modifications, including cross-links (29,37).…”
Section: Fig 4 Phototoxicity Of Lipofuscinmentioning
confidence: 99%
“…In AMD, CEP adducts are elevated in Bruch membrane (27), the extracellular matrix separating the RPE from the blood-bearing choroid; AMD plasma also contains elevated levels of CEP adducts and CEP autoantibodies (34). Furthermore CEP adducts stimulate neovascularization in vivo (35) and can induce a late stage AMD-like phenotype (geographic atrophy) in a mouse model of AMD (36). Iso [4]LGE 2 , an extraordinarily reactive electrophile belonging to the isolevuglandin family, is generated by free radical-induced oxidation of arachidonyl phospholipids and produces an array of lysyl modifications, including cross-links (29,37).…”
Section: Fig 4 Phototoxicity Of Lipofuscinmentioning
confidence: 99%
“…9) that accumulate in the retinas of individuals with age-related macular degeneration (37,38). CEP-modified proteins promote angiogenesis, leading to choroidal neovascularization in the retina, a pathological development that is associated with the advanced stages of age-related macular degeneration (21). In view of the unique biological involvements of ghydroxyalkenal OxPCs, such as HOHA-PC, and the potential for these and other activities of the analogous g-hydroxyalkenal OxPAFs, it is important to understand the reactions that consume them.…”
Section: Structure Confirmation Through Derivatization Of Oxpafsmentioning
confidence: 99%
“…Most recently, it was found that the modification of proteins by a g-hydroxyalkenal OxPC, the 4-hydroxy-7-oxo-5-heptenoate ester of 2-lysophosphatidylcholine (HOHA-PC), produces carboxyethylpyrroles (CEPs) that incorporate the e-amino group of lysyl residues. CEPs accumulate in the retinas of individuals with age-related macular degeneration, where they promote choroidal neovascularization (21). They also promote angiogenesis in rat cornea (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mice immunized with mouse serum albumin (MSA) adducted with CEP (CEP-MSA) develop an atrophic AMD-like phenotype including RPE loss and drusen formation with accumulation of macrophages in the interphotoreceptor matrix and C3 fragments in Bruch's membrane (Hollyfield et al, 2008). CEP-MSA also stimulates angiogenesis in ex-vivo models and subretinal injection of CEP-MSA exacerbates laser-induced CNV in mice (Ebrahem et al, 2006). These observations definitely implicate oxidized lipid adducts in the perturbation of RPE cell function, leading RPE cell death both in vitro and in vivo.…”
Section: Carboxyethyl Pyrole (Cep) Adductsmentioning
confidence: 99%